Mastering New Testament Greek : Essential Tools for Students - Robinson, Thomas A. ([Grand Rapids, Mich. : Baker Academic], 2007)
Learning New Testament Greek can be a daunting task. In Mastering New Testament Greek: Essential Tools for Students, with CD-ROM, Thomas A. Robinson offers learners an inventive set of tools that can be used alongside their beginning grammar text to help them move toward Greek mastery. At the heart of Robinson's ingenious vocabulary mastery system are his Cognate Groups that link Greek words together based on their common roots, enabling those desiring to learn Greek to build a working vocabulary more quickly and easily. Additional vocabulary-building tools in Mastering New Testament Greek include: a comprehensive list of words that are identical in English and Greek; detailed explanations of Greek suffixes and prefixes; a familiar list of English words derived from Greek roots; a helpful cognate Greek-English dictionary. Mastering New Testament Greek, the revised and expanded third edition of Robinson's well-received Mastering Greek Vocabulary, now includes an Index of Greek Word Endings that enables those studying Greek to decode baffling grammatical forms, as well as an innovative collection of charts that illustrate the correlations between Greek prepositions and the cases they use to complete their meanings. Mastering New Testament Greek also comes with a CD-ROM packed with user-friendly software programs that support and expand the utilities contained in the book. Software modules guide users in: mastering the Greek alphabet and pronunciation; learning new vocabulary; reviewing Greek verbs; parsing difficult grammatical forms. Taken together, the tools contained in Mastering New Testament Greek and in the accompanying CD-ROM comprise an essential toolkit that students of the language of the New Testament, from beginning to advanced, will not want to be without. - Publisher.
Introduction -- Instructions -- Identical Greek/English words -- Cognate groups -- Explanation of Greek prefixes and suffixes -- Identical Greek/English prefixes and suffixes -- Derived English words -- Mini Greek-English cognate dictionary -- Prepositions and cases -- Appendix 1 : Grimm's law -- Appendix 2 : Common pronouns, adjectives, and adverbs.
"As of Oct. 1, 2010, HP ISBN 9781565635760, Mastering New Testament Greek w/CD, is available from Baker Pub Group under their ISBN 9780801047558." - Hendrickson website.
Book has Hendrickson publication information, including ISBN 9781565635760, on t.p. and t.p. verso. On back cover, Hendrickson publication information is covered with Baker Academic stickers, including ISBN 9780801047558.
Keywords: Bible. -- Language, style; Biblical Greek language -- Greek Vocabulary; New Testament Greek language -- Greek Grammar